Digitalization of audit actions in the Industry 4.0 era - Wierzbic, Arkadiusz; Szewczyk, Karol (Cyfryzacja działań auditowych w dobie przemysłu 4.0, 2019)
This digitalisation in the broad sense is not only about the processes that create added value, but also about the supporting processes. The activities of the quality management process are interesting in this regard. The purpose of the article is to examine the changes taking place in enterprises during the fourth industrial revolution in the area of the Layered Process Audit, i.e. a tool used to verify the functioning of processes against accepted standards. The article presents a brief description of this tool, as well as an example of a solution from the automotive industry functioning at the Robert Bosch Mirków plant. In addition, the results of surveys conducted in the group of process managers and auditors indicating the advantages of such an approach and areas for improvement were cited
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 4 (54), s. 74-87
Keywords: informatyka ekonomiczna